Smart Grid A New Paradigm to Power Grid & Marketing Opportunity in Developing Countries (The International Research Journal of Management Science, 2016)
The smart grid has been using more and more power electronic devices as an improvement to the current electrical power system along with plug-and-play integration of alternating sources of power. It has adopted the latest wired/wireless technologies incorporated into electric devices for timely information flow, control and on-demand interaction with customers. So, smart grid is reliable, efficient, and user as well as environment friendly. The grid keeps on getting smarter with better availability of new materials, storage systems, and alternative sources of energy. Though, this paper encompasses all sectors of smart grid, not limited to, smart transmission line, smart distribution generation, smart storage, smart communication, cyber security, and environment friendliness, it has demonstrated the wireless prototype of remote interaction between the consumers and the utility company. In countries like Nepal where power grid infrastructure is limited mostly to cities and energy supply is far below its demand, there is a great potential for energy market growth having minimal barriers to renewables.